Advantages of the use of computational resources in the analysis of the structures and the importance of the engineer in the simplified analytical models layout - Filho, João Pereira de Souza; Porto, Thiago Bomjardim; Oliveira, Danilo Bento (Revista Hipótese, 2019)
The objective of this work is to compare the efforts of slabs, beams and pillars obtained analytically from a hypothetical case study of a small building with four slabs, six beams and nine pillars, with the results obtained in commercial software using finite element method. The results were satisfactory, with relative errors less than 35%. Besides the analytical results obtained, this research is alert to the importance of the manual conferences for the validations of numerical computational models.
Keywords: Numerical Analysis; Finite Element Methods (FEM); Structures